Intervensi Perawatan Luka dengan Irigasi pada Pasien DM Tipe II (Journal of Telenursing (JOTING), 2023)
The research aims to determine the effectiveness of wound care interventions using the irrigation method in type 2 DM patients at Al-Ihsan Hospital Bandung. This research method uses a Quasy Experiment one group pretest and posttest design approach using a random sample of 7 respondents and following operational standards. The results of the study, before and after the intervention, were assessed using the BJWAT Bates-Jensen wound assessment tool to assess whether there was a decrease in the degree of injury or not, from the first session and the second assessment session. The intervention was carried out during 2 wound treatments. From the results of statistical tests, it was found that there was a significant difference in the results of the first assessment and the second assessment before and after wound treatment with irrigation with a p-value of 0.001 (P